STRATEGI PERENCANAAN DAN PENGEMBANGAN OBJEK WISATA (STUDI KASUS PADA OBJEK WISATA KALI TOPA DESA WASUEMBA KECAMATAN WABULA KABUPATEN BUTON - La Sudarman; Nurlia Udin (Management Insight: Jurnal Ilmiah Manajemen, 2021)
The research objective is to identify and analyze the planning and development strategies of tourism objects (case study on the Kali Topa tourist attraction, Wasuemba Village, Wabula District, Buton Regency. The research method is to use quantitative research. The data used are secondary and primary data. The data analysis used SWOT analysis and software. SPSS version 20. The sampling technique used simple random sampling in the Kali Topa tour. The results showed that the driving factors were divided into two, namely strength and opportunity as well as compressed inhibiting factors from weaknesses and threats. the existence of business development by the surrounding community. Meanwhile, the inhibiting factor of public awareness of tourism and other tourist destinations. The development strategy for Kali Topa Tourism Object is based on various aspects of development such as tourists, transportation, attraction of tourist objects. owned, supporting facilities and infrastructure in the environment of tourist objects, the use of telecommunications as a promotional media, and supported by quality funds and human resources; The development strategy is carried out as an effort to increase the visit of the Kali Topa Tourism Object every year.